Relation between participating in playgroup with child development - Elsa Maimon Djauhar Ismail Mei Neni Sitaresmi (Journal of the Medical Sciences (Berkala Ilmu Kedokteran), 2012)
Playgroup is one of early education programs to promote child development. A cohort study found that early education program resulted in better social performance. However this study did not evaluate the influence of this program on child development. The aim of this study was to evaluate whether participating in playgroup relates to child development achievement. This was a cross sectional study conducted on children in Yogyakarta Special Region. The subjects were children in the first month of kindergarten. The child development was tested using Denver II. Other data were collected by questioners and filled by their parents. Chi-square test was used to analyze the factorsthat influenced the child development. One hundred and seventy two children participated in the study. It was found that the development achievement of children participating in playgroup were 3.2 times better than those not participating in playgroup (p=0.002; OR: 3.248; 95% CI: 1.558-6.774), whereas gender, education of parents, number of slibings, and birth weight were not associated with the child development achievement. In conclusion, joining the playgroup relates to the child achievement development.Keywords: playgroup - child development - Denver II test - kindergarten - education